Teacher Features and the Involvement of Students Learning Process - Emina Kapić (Društvene i Humanističke Studije, 2019)
This empirical research deals with the characteristics of teachers and the involvement of students learning process. The standardized instruments were used in the research: TF– teacher features and SIILP– student involvement in learning process. The research was done on a sample of 120 students of ninth grade of elementary schools. The aim of the research was to examine which teacher features influence student involvement in learning. The T-test of independent samples are compared to the results of the examination of students' involvement in learning process according to dominant teacher traits of authoritativeness–cooperativeness, normativity–focus on problem solving, and emotionally positive reactions–emotionally negative reactions. The results of the research showed that there was no significant difference between the total involvement of students in learning process on dominant characteristics of teachers like authoritativeness–cooperativeness, normativity–focus on problem solving and emotionally positive reactions–emotionally negative reactions. There was also no significant difference in the impact of teacher's dominant traits and in the success in student involvement in learning process. It was as well shown that there was no significant difference in the influence of dominant teacher traits like authoritativeness–cooperativeness, emotionally positive reactions–emotionally negative reactions and gender on student involvement in learning process. Only the common influence of the dominant traits of teachers normativity–orientation on problem solving and gender on the involvement of students in teaching was statistically significant. Also, the gender impact on student involvement in teaching was statistically significant as well.